VALUASI EKONOMI ALTERNATIF TEKNOLOGI PENGELOLAAN SAMPAH PERKOTAAN - Haikal Rahman (Quantitative Economics Journal, 2012)
This study is specifically aims to elaborate  on the  economic valuation  that  consists of: (1) Investment costs and (2) Operating  Costs of the alternative  waste  management technology which can be applied to the final processing of Municipalities Solid Waste. The results of the simulation shows that the Biodrying with the combination of Incenerator or Gasification is the technology that has the least operational costs with an average of 10.907 million Euro per year of its operational costs. On the other hand the Aerobic MBT (Mechanical Biological Treatment) without the production of RDF (refuse Derivative Fuel) technology is a technology that requires the highest operational costs with an average of 15,808 million Euro per year. In terms of the initial investment costs both Biological Treatment technology has the lower value compare to the two Thermal Treatment technologies.